2002
DOI: 10.1075/sll.5.1.10pic
|View full text |Cite
|
Sign up to set email alerts
|

Word order variation and acquisition in American Sign Language

Abstract: Summary of the dissertationThis study examines two crosslinguistic generalizations generated by previous studies of word order: (1) that the word order parameters (i.e. the spec-head and headcomplement parameters) are universally set early, and (2) that word order variation in languages with rich and regular inflection is acquired earlier than in languages with poor or irregular inflection. These generalizations are evaluated using spontaneous production data of four deaf children between the ages of~20-30 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…They selected various morphosyntactic structures based on their reported developmental timecourse in ASL acquisition. This included ASL structures which have been claimed to be acquired relatively early (by age 2;6–3;0), such as basic word order with plain verbs (Pichler, 2002) and negation and ‘agreement’ verbs6 (Anderson & Reilly, 1997; Meier, 1987). Boudreault and Mayberry also included structures reportedly acquired later such as wh-questions, relative clauses, and ‘classifier’ constructions 7.…”
Section: Asl Grammaticality Judgement Task (Boudreault and Mayberry 2006)mentioning
confidence: 99%
“…They selected various morphosyntactic structures based on their reported developmental timecourse in ASL acquisition. This included ASL structures which have been claimed to be acquired relatively early (by age 2;6–3;0), such as basic word order with plain verbs (Pichler, 2002) and negation and ‘agreement’ verbs6 (Anderson & Reilly, 1997; Meier, 1987). Boudreault and Mayberry also included structures reportedly acquired later such as wh-questions, relative clauses, and ‘classifier’ constructions 7.…”
Section: Asl Grammaticality Judgement Task (Boudreault and Mayberry 2006)mentioning
confidence: 99%
“…Deaf children who learn signed language from birth reach milestones such as babbling, word order acquisition and wh-question production at the same time as hearing children who learn spoken language from birth (Lillo- Martin, 2000;Petitto, Holowka, Sergio, & Ostry, 2001;Pichler, 2001). Moreover, similar brain regions, including the left inferior frontal cortex, superior temporal cortex and planum temporale, are used to comprehend signed and spoken language, despite the fact that initial processing occurs in distinct regions for each language modality (primary and secondary visual and auditory cortices for speech; posterior occipoto-temporal regions for signed language; Corina, Vaid, & Bellugi, 1992;Emmorey et al, 2003;Petitto et al, 2000).…”
mentioning
confidence: 99%
“…Recently, Palmer (2015) compared the acquisition of ASL canonical and non-canonical word orders of four bimodal bilinguals, two Kodas and two implanted DDs whose ages ranged from 1;8 to 3;6. While both the Kodas and DDs produced canonical SV and VO orders as early as 23 months, suggesting an early setting of Spec-Head and Head-Complement parameters, they showed little use of non-canonical OV and VS orders when compared with the Deaf controls as reported in Chen Pichler (2001). …”
Section: Introductionmentioning
confidence: 64%
“…In the early literature on ASL acquisition, canonical SVO and derived word orders are observed to emerge at an early age among DDs (Newport and Meier, 1985; Lillo-Martin, 1999; Chen Pichler, 2001). However, Lillo-Martin and Berk (2003) found that the two DHs in their study, who were not exposed to an accessible language like ASL until after age 5, had no problem acquiring the canonical SVO order but seldom attempted derived word orders that reflected grammatical dependencies and erred more when they did so.…”
Section: Introductionmentioning
confidence: 99%